PENERAPANÂ METODEÂ BERMAINÂ PERANÂ UNTUKÂ MENINGKATKANÂ AKTIVITASÂ DANÂ HASILÂ BELAJARÂ SISWAÂ KELASÂ VÂ PADAÂ MATAÂ PELAJARANÂ IPSÂ POKOKÂ BAHASANÂ JENISâ€JENISÂ USAHAÂ EKONOMIÂ DIÂ SDNÂ NGADILUWIHÂ 02Â KEDIRIÂ - zulfa nairurohmah; Chumi Zahroul (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
TheÂ  SocialÂ  ScientsÂ  SubjectÂ  learningÂ  activitiesÂ  inÂ  SDNÂ  NgadiluwihÂ  02Â  KediriÂ  yetÂ  usingÂ  a varietyÂ  ofÂ  learningÂ  methods.Â  AccordingÂ  toÂ  theÂ  observationÂ  ofÂ  prasiklusÂ  knownÂ  thatÂ  the activityÂ  andÂ  studentÂ  learningÂ  outcomesÂ  haveÂ  notÂ  beenÂ  includedÂ  inÂ  bothÂ  criteria. PrecentationÂ ofÂ studentÂ activity inÂ theÂ prasiklusÂ inÂ highlyÂ activeÂ criteriaÂ is12%Â (3Â students), inÂ theÂ activeÂ criteriaÂ isÂ 16%Â (4Â students),Â inÂ theÂ quiteÂ activeÂ criteriaÂ isÂ 56%Â (14Â students),Â in theÂ  lowÂ  activeÂ  criteriaÂ  isÂ  16%Â  (4Â  students).Â  TheÂ  meansÂ  ofÂ  studentÂ  learningÂ  activityÂ  in prasiklusÂ  isÂ  56%Â  (quiteÂ  activeÂ  criteria).Â  PrecentationÂ  ofÂ  studentÂ  learningÂ  outcomesÂ  inÂ  the veryÂ goodÂ criteriaÂ isÂ 24%Â (6Â students),Â inÂ theÂ goodÂ criteriaÂ isÂ 24%Â (Â 6Â students),Â inÂ theÂ good enoughÂ  isÂ  36%Â  (9Â  students),Â  inÂ  theÂ  notÂ  goodÂ  isÂ  16%Â  (4Â  students).Â  TheÂ  meansÂ  ofÂ  student learningÂ  outcomesÂ  inÂ  prasiklusÂ  isÂ  68Â  (goodÂ  enoughÂ  criteria).BasedÂ  onÂ  theseÂ  findingsÂ  the needÂ  forÂ  aÂ  moreÂ  variedÂ  teachingÂ  methodsÂ  withÂ  emphasisÂ  onÂ  studentÂ  activityÂ  andÂ  provide opportunitiesÂ  forÂ  studentsÂ  toÂ  developÂ  theirÂ  learningÂ  abilitiesÂ  toÂ  theÂ  fullest.Â  InÂ  accordance withÂ  theseÂ  problems,Â  theÂ  goalÂ  ofÂ  thisÂ  researchÂ  isÂ  toÂ  improveÂ  theÂ  activityÂ  andÂ  student learningÂ  outcomesÂ  inÂ  classÂ  VÂ  throughÂ  theÂ  applicationÂ  ofÂ  learningÂ  methodsÂ RoleÂ  PlayingÂ IPS HighlightsÂ  TypesÂ  ofÂ  economicÂ  activitiesÂ  in SDNÂ  NgadiluwihÂ  02Â  Kediri.Â  ThisÂ  typeÂ  ofÂ  research isÂ classroomÂ actionÂ researchÂ (PTK)Â areÂ conductedÂ inÂ twoÂ cycles.Â TheÂ resultsÂ obtainedÂ inÂ this studyÂ  indicateÂ  thatÂ  throughÂ  theÂ  implementationÂ  ofÂ  RoleÂ  PlayingÂ  methodÂ  canÂ  increaseÂ  the activityÂ  andÂ  studentÂ  learningÂ  outcomes.Â  TheÂ  averageÂ  activityÂ  ofÂ  studentsÂ  inÂ  prasiklusÂ  is 56,4%Â  (quiteÂ  activeÂ  criteria).Â  InÂ  theÂ  firstÂ  cycleÂ  increasedÂ  toÂ  70,8%Â  (activeÂ  criteria).Â  InÂ  the secondÂ  cycleÂ  increasedÂ  againÂ  toÂ  80,96%Â  (highlyÂ  activeÂ  criteria).Â  TheÂ  meansÂ  scoreÂ  onÂ  the studentÂ  learningÂ  outcomesÂ  prasiklusÂ  isÂ  68Â  (criteriaÂ  quiteÂ  well).Â  InÂ  theÂ  firstÂ  cycleÂ  increased toÂ 73.2Â (goodÂ criteria).Â InÂ theÂ secondÂ cycleÂ increased againÂ toÂ 83.18Â (veryÂ goodÂ criteria). Â Keywords:Â  RoleÂ  PlayingÂ  Method,Â  studentÂ  lerningÂ  activity,Â  studentÂ  learningÂ  outcomes, classroomÂ actionÂ research. Â